Cenozoic thermal history reconstruction of the Dongpu Sag, Bohai Bay Basin: Insights from apatite fission‐track thermochronology. (27th February 2019) - Tang, Xiaoyin; Zuo, Yinhui; Kohn, Barry; Li, Yi; Huang, Shaopeng
Abstract: Knowledge of the thermal history of the onshore Dongpu Sag (DPS), Bohai Bay Basin is important for understanding its tectonic development within a broader regional context and for elucidating its poorly studied source‐rock maturation history. To unravel DPS time‐temperature development, apatite fission‐track data were acquired from eight sandstone samples in three deep wells. Thermal history modelling indicates continuous heating during the rifting stage (early Eocene to late Oligocene), followed by cooling attributed to tectonic uplift between ~27 and ~16 Ma, which resulted in the removal of ~1, 400 to 1, 800 m of section. Reheating occurred during the subsidence stage from middle Miocene until present. Unlike typical passive continental margin basins, the DPS experienced accelerated post‐rifting subsidence from ~5.8 Ma, which was especially marked since ~2.6 Ma. This phase was probably triggered by normal fault reactivation, in combination with a variation in the deep heat flow pattern.